2015
DOI: 10.1016/j.ijdevneu.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Systematic differences in time of cerebellar‐neuron origin derived from bromodeoxyuridine immunoperoxidase staining protocols and tritiated thymidine autoradiography: A comparative study

Abstract: As exogenous markers of DNA synthesis, 5-bromo-2'-deoxyuridine (BrdU) and tritiated thymidine ([(3)H]TdR) have revolutionized our ability to identify proliferating neuroblasts and follow their fate during the development of the central nervous system. The effect of the incorporation of these molecules into DNA on cell proliferation, migration and differentiation is frequently neglected (Duque and Rakic, 2011. J. Neurosci. 31, 15205-15217). By a progressively delayed cumulative labeling method, the current pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…After this treatment, they were injected several times with 6 mg of 5bromo-2´-deoxyuridine (BrdU) in accordance with the procedure of Sekerkova et al [61]. This marker was delivered following a progressively delayed labeling comprehensive procedure [37,57] Our results revealed no signs of toxicity in the pregnant dams after HU treatment.…”
Section: Embryonic Effects Of Hu Exposure: Long-survival Experimentsmentioning
confidence: 79%
“…After this treatment, they were injected several times with 6 mg of 5bromo-2´-deoxyuridine (BrdU) in accordance with the procedure of Sekerkova et al [61]. This marker was delivered following a progressively delayed labeling comprehensive procedure [37,57] Our results revealed no signs of toxicity in the pregnant dams after HU treatment.…”
Section: Embryonic Effects Of Hu Exposure: Long-survival Experimentsmentioning
confidence: 79%
“…These observations indicate that the degree of damage induced by HU may influence the level of abnormalities in the cerebellum. As PCs and DCN neurons are the first cells that arise from the neuroepithelium [36,41,42] and the time windows of HU exposure (from E13 to E15) correspond with the developmental timetables of these neurons [36,56], we propose that several PCs and DCN neurons may have never been produced.…”
Section: Embryonic Effects Of Hu Exposure: Short-survival Experimentsmentioning
confidence: 99%
“…After this treatment, they were injected several times with 6 mg of 5-bromo-2’-deoxyuridine (BrdU) in accordance with the procedure of Sekerkova et al [60]. This marker was delivered following a progressively delayed labeling comprehensive procedure [36,56] that consisted of injecting pregnant dams in an overlapping series, in accordance with the following time-windows: E13–14, E14–15, E15–16 … E19–20. The offspring were sacrificed at postnatal day 90 (P90) and several cerebellar features were quantified, per section, in each cerebellar cortex compartment (vermis, paravermis, and medial and lateral hemisphere), or alternatively in each deep nucleus (fastigial, interposed and dentate): The area of the cerebellum, length of the cerebellar cortex, ML area, PC number, GC number, area of the IGL, area of the white matter, the areas of the cerebellar nuclei, and number of DCN neurons.…”
Section: Embryonic Effects Of Hu Exposure: Long-survival Experimentsmentioning
confidence: 99%
“…One of the most regular features of the CNS development is that each neuronal population is generated during a specific temporal window, the neurogenetic timetable, (Bayer and Altman, ; Martí et al, , ). It has now been demonstrated that neurogenesis does not stop abruptly at birth, but it continues in specific brain regions throughout life in many species, including human (Gage, ).…”
Section: Adult Neurogenesismentioning
confidence: 99%